Uulul Albaab dalam Perspektif Al-Qur’an - Salam, Eka Fitra Ramadani; Miswar, Andi; Halimah, Halimah (Jurnal el-Huda, 2025)
In the Quran there are 16 verses called Uulul Albaab; Muslim scholars understand, define, and describe "Uulul Albaab" in different ways. Because if it is translated as "a person of reason" alone, it is still not entirely correct. The word "uulu" means a person who has, and "albaab" is the plural of the word "lubb," which means essence, which can be used to describe things like reason, heart (taste), and so on. It is considered important to conduct this study because ulul albab is mentioned in the Quran in many places, and its many presences must have a deep meaning. In this literature study, the thematic interpretation method is used; a theme of ulul albab is chosen as the basis for understanding His verses. The purpose of this study of ulul albab verses is to determine the attitudes and characteristics that must be possessed by an ulul albab (Muslim scholar) according to the Quran. By using this thematic approach, the attitudes and characteristics of ulul albab will become clear. Furthermore, the conclusion from the interpretation of the verses of ulul albab is that a Muslim scholar must understand the attitudes and characteristics of ulul albab so that they can work well.